Hydrogen Bonding with Hydridic Hydrogen-Experimental Low-Temperature IR and Computational Study: Is a Revised Definition of Hydrogen Bonding Appropriate? - Civiš, Svatopluk; Lamanec, Maximilián; Špirko, Vladimír; Kubišta, Jiří; Špet'ko, Matej; Hobza, Pavel (Journal of the American Chemical Society, 2023)
Spectroscopic characteristics of Me3Si-H···Y complexes (Y = ICF3, BrCN, and HCN) containing a hydridic hydrogen were determined experimentally by low-temperature IR experiments based on the direct spectral measurement of supersonically expanded intermediates on a cold substrate or by the technique of argon-matrix isolation as well as computationally at harmonic and one-dimensional anharmonic levels. The computations were based on DFT-D, MP2, MP2-F12, and CCSD(T)-F12 levels using various extended AO basis sets. The formation of all complexes related to the redshift of the Si-H stretching frequency upon complex formation was accompanied by an increase in its intensity. Similar results were obtained for another 10 electron acceptors of different types, positive σ-, π-, and p-holes and cations. The formation of HBe-H···Y complexes, studied only computationally and again containing a hydridic hydrogen, was characterized by the blueshift of the Be-H stretching frequency upon complexation accompanied by an increase in its intensity. The spectral shifts and stabilization energies obtained for all presently studied hydridic H-bonded complexes were comparable to those in protonic H-bonded complexes, which has prompted us to propose a modification of the existing IUPAC definition of H-bonding that covers, besides the classical protonic form, the non-classical hydridic and dihydrogen forms.